DISTANCE BETWEEN THE STYLOMASTOID AND JUGULAR FORAMENS IN PEOPLE WITH DIFFERENT CRANIAL INDICES - Kerimzade, G.E. (World of Medicine and Biology, 2023)
The purpose of the study was to determine the distance between the stylomastoid and jugular foramina on dry skulls of people with different cranial indices. The study was conducted on 159 dry skulls. On all skulls, the length and width of the skull were measured using a sliding ruler, and then all skulls were divided into the following groups: brachiocranes, dolichocranes and mesocranes. The obtained data were recorded and subjected to statistical processing. When statistically analyzing the distance between the stylomastoid foramen and the jugular foramen in skulls of different shapes in terms of width, it was found that in all skulls this indicator shows high differential reliability. The distance between the stylomastoid and jugular foramina does not have clear differences on the right and left, but differs significantly in skulls with different indices. Moreover, in dolichocranes this size is larger than in brachiocranes and mesocranes.
Keywords: stylomastoid foramen; jugular foramen; dolichocrane; brachiocrane; mesocrane